O cuidado de si de pessoas com insuficiência renal crônica em tratamento conservador - Roso, Camila Castro (2012)
The incidence of people with chronic renal failure has increased significantly, reaching alarming numbers of individuals with kidney failure. This is a disease that affects kidney function and disables the maintenance of internal homeostasis of the organism. Treatment often causes frustration and limitations due to the various dietary restrictions and changes in lifestyle, which requires the patient to participate in their own treatment, determining its autonomy. Thus, this following research aimed to describe how people with chronic renal failure on conservative treatment take care of themselves and identify the possibilities and limits of self-care of people with chronic renal failure undergoing conservative treatment. It is a descriptive qualitative field research, which has taken place in the Uremia Clinic at the University Hospital of Santa Maria. The study included 15 people with chronic renal failure undergoing conservative treatment who attended the clinic. Data collection was performed through narrative interview supplemented by consulting the medical records of patients. The method of analysis of data was through theme analysis, which is a specific form of content analysis proposed by Minayo. All ethical aspects have been respected according to Resolution 196/96 of the National Health Board. The data were organized into two categories, first, the daily life of people with chronic renal failure undergoing conservative treatment as a possibility for self-care, was unveiled on the themes: the experience of self-care of persons with chronic renal failure on conservative treatment, autonomy in self-care of people in the conservative treatment and family support as a possibility of self-care in the conservative treatment. The second category called the limits of self-care of persons with chronic renal failure undergoing conservative treatment, had the following topics: the progress of the disease and care dependency, and the limits and the impact of conservative treatment in chronic renal failure. It is understood that the results of this research might contribute to the care of people with chronic renal failure on conservative treatment and in the manifestation of their autonomy through self-care. It is due to the health team to think and act in promoting the health of those with an eye toward autonomy in health education activities in the pursuit of quality of life.